Ta'lîmu Ashwâti al-Lughah bi at-Tharîqah al-Tarkîbiyyah al-Tahlîlîyyah li Mahârati al-Istimâ' li al-Thullâb al-Mubtadiîn - Khozaimah Khozaimah (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2021)
Dar al-Lughah Wa Dirasat al-Islamiyyah Pamekasan Islamic boarding school is an Arabic language development institutions which applies phonetics learning to students at the first grade. Phonetic learning is important in learning Arabic especially for listening skill. Arabic phonetics and listening skill are an inseparable unity. First graders need to learn phonetics to support their listening skills in learning Arabic. At Dar al-Lughah, this is taught using synthetic-analytical methods (al-thariqah al-tarkibiyyah al-tahliliyyah) as it is considered very effective. The results of observations, interviews, questionnaires and document examination through descriptive qualitative methods show that the use of synthetic-analtical method is very suitable for phonetics subject learning among first graders of Dar al-Lughah. Moreover, several media are used. One of with is schematic drawing of the face (rasm al-takhthithi li al-wajhi). However, some problems arise in the process of phonetics learning, including:1) First graders are not accustomed to recite any sounds of Arabic letters, words or sentences in good and right pronounciation.2) First graders find it difficult to harden the tongue in pronouncing some specific sounds of Arabic letters, especially those which do not exist in Indonesian language, 3) Most of first graders come from schools where they were not used to listen to Arabic letter pronunciation from native speakers.